"Surviving and Thriving": An Autoethnography of a Black Afro-Caribbean Early Career Teacher in a Northern Ontario First Nation Community - Patricia Briscoe; Jody-Ann Robinson (University of Windsor, 2024)
The beginning years of a teacher's career can be an overwhelming experience, and combined with being in an isolated, fly-in community, particularly during a pandemic, can be debilitating. This qualitative research is aimed to support and account for the story of a Black Afro-Caribbean, early career teacher (ECT) in a Northern Ontario First Nation (FN) community over a three-year teaching placement. The goals were to use her stories for reflection, inspiration, and guidance to support other ECTs, and to provide recommendations to teacher-education programs to lessen attrition and increase retention among ECTs in FN school placements. An autoethnographic method was used to identify key themes in her narratives to better understand her experiences of surviving and thriving. Although this ECT was significantly tested about her decision to become a teacher, support, empathy, resiliency, and governing one's practice with clearly defined moral and ethical principles rooted in the belief that every child can learn helped her survive and thrive. The conclusion was that ECTs in FN school placements need, among other things, a willingness to be vulnerable and resilient.